STRUCTURAL DEVELOPMENT OF MOSQUE BUILDING BASED ON ADDITIONAL CAPACITY OF PRAYER ROOM - Lutfi, Muhamad; Chayati, Nurul; Adriansyah, Asrul (ASTONJADRO, 2021)
Mosques serve as a place of worship and foster Muslims who live around the mosque, so the function of this can give a positive impact for Muslims’ life. Mosques also function as a place for developing people’s activities from the time of Prophet Muhammad to the present. It certainly plays important roles so the condition of the mosque, especially the interior, needs to have comfort element in order to get more solemnity when carrying out those activities. Mosque Al-Hidayah is located in Kampung Belentuk RT 001 RW 001, Kelurahan Cimahpar, Kecamatan Bogor Utara, Kota Bogor. This Belentuk village area has a land area of 23 hectares with a Muslim population of 1571 and 807 of them are men. This village has three mosques which Masjid Al-Hidayah is one of them. At this time, mosque Al-Hidayah has land area of 339 m2 with a building area of 128,9 m2 so that the room capacity can only accommodate 106 people. The number of men of Kampun Belantuk are divided into those three mosques of the village, even so, Mosque Al-Hidayah is not able to accommodate the number of people especially on Friday prayer because the number of worshipers is more than the current capacity of the mosque. The result of the analysis shows the need for prayer space is 330 m2 to accommodate 270 worshipers in prayer activities, especially Friday prayers, then the result of the analysis of the existing concrete structure were carried out by means of a concrete bounce test using the Hammer test, it is known that the average value of the concrete quality in the column is fc’=13.34 MPa, the block is equal to fc’=14.41 MPa. It indicates that the quality of the existing concrete of the Al-Hidayah Mosque does not meet the requirements of SNI 2847-2019 Article 19.2 concerning the minimum allowable normal concrete quality, then the design is carried out according to space requirements and a structural analysis is carried out on the planned design. The planned design is based on the existing space and land requirements which are 15 m x 14 m with a height of 3.5 m per floor and structural analysis is declared safe.